UJI DIAGNOSTIK UJI DIAGNOSTIK PEMERIKSAAN NITRIT DENGAN KULTUR URIN PADA SUSPEK INFEKSI SALURAN KEMIH - putra rahmadea utami (Klinikal Sains : Jurnal Analis Kesehatan, 2021)
Urinary tract infection (UTI) is the second largest infection after respiratory infection and can cause sepsis. Urinary tract infections occur due to the entry of microorganisms in the urinary tract. The urinary tract that is usually infected is the urethra (urethritis), bladder (cystisis), ureter (ureteristis), kidney tissue (pyelonephritis). This study aims to determine the sensitivity and specificity of the diagnostic test of nitrite examination with urine culture in suspected urinary tract infections. The method of this study is a descriptive-analytical study with a cross-sectional retrospective approach, conducted in the STIKes field laboratory with the population studied in this study were all patients diagnosed with urinary tract infection with a sample size of 50 samples. The results of this study showed positive nitrite results as many as 17 people, 34% percentage, and negative nitrite results as many as 33 people with a percentage of 66% and on urine culture examination obtained positive results as many as 17 people with a percentage of 34%, which results in growth of bacterial colonies on cultures> 100,000 CFU / mL and negative results of 33 people with a percentage of 66%. Sensitivity Results 82%, Specificity 90.9%. The conclusion of this study is the value of sensitivity, high specificity so that the nitrite test with urine culture can be applied to help diagnose UTI.